Zbarvení srsti kočkovitých šelem (Felidae) - Pavliska, Petr (Jihočeská univerzita, 2008)
The coat colouration has been studied in the family Felidae. I have tried to describe a structure, composition and marks of the mammalian coat and to show possible changes of the colouration based on my own direct observations. Finally I have made a getting methodology of photographic data for possible application in the species- and individual- identification in felids. This study is based on the literal review and personal observations in the zoological gardens (especially in the Czech Republic). This review offers to me some hypothese for future investigation.
The coat colouration of Felidae
Keywords: zbarvení; srst; šelmy; kočkovité šelmy; Felidae; Carnivora; colouration; coat; fur; felid; Felidae; Carnivora